2023
DOI: 10.3389/fnagi.2023.1132808
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic correlates of serum neurofilament light chain levels in amyotrophic lateral sclerosis

Abstract: ObjectiveTo investigate the relationship between serum levels of the neuroaxonal degeneration biomarker neurofilament light chain (NFL) and phenotype in ALS.Materials and methodsSerum NFL (sNFL) concentration was quantified in 209 ALS patients and 46 neurologically healthy controls (NHCs).ResultssNFL was clearly increased in ALS patients and discriminated them from NHCs with AUC = 0.9694. Among ALS patients, females had higher sNFL levels, especially in case of bulbar onset. sNFL was more increased in phenotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…9,11 Another study showed that serum NfL was not significantly different between early and late symptomatic phases. 15 In contradiction to previous studies, 30,31 we found no correlation between disease severity and NfL levels in ALS. This might be explained by discrepancies between cohorts, as we excluded patients with bulbar symptomatology or pronounced UMN involvement.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…9,11 Another study showed that serum NfL was not significantly different between early and late symptomatic phases. 15 In contradiction to previous studies, 30,31 we found no correlation between disease severity and NfL levels in ALS. This might be explained by discrepancies between cohorts, as we excluded patients with bulbar symptomatology or pronounced UMN involvement.…”
Section: Discussioncontrasting
confidence: 99%
“…Both components are reflected in the ALSFRS-R score as measures of disease severity, and they are additionally known to be related to higher neurofilament levels. [31][32][33] Similarly, in MMN, we found no or weak, not relevant, correlations of serum NfL with disease duration and disease severity. This is in agreement with other studies on NfL levels in various forms of neuropathy, demonstrating NfL is only minimally elevated, 16,18 is not correlated to disease duration 34,35 and NfL levels are stable upon treatment.…”
Section: Discussionmentioning
confidence: 45%
See 1 more Smart Citation
“…Considering that rising NfL levels signal the early onset of neural injury as well as many neurological complications (Ferreira-Atuesta et al, 2021;Verde et al, 2023), these data indicate that the HDBR is an effective model for weightlessness exposure in relation to neurological insults to the brain. We hypothesized that the headward fluid shifts observed in HDBR would predispose participants to this type of injury.…”
Section: Neural Injury (Nfl Gfap)mentioning
confidence: 90%
“…These patients did not present any clinical signs or changes in neurofilament light chain (NfL) blood levels. NfL is considered as a good biomarker to define the presymptomatic stage in ALS as its elevation often precedes motor deficits [46,47]. Strikingly, the authors showed that presymptomatic ALS gene carriers display abnormal body composition, indicating elevated catabolism and loss of metabolically active cells compared to metabolically active tissue.…”
Section: Early Involvement Of Metabolic Abnormalities In Amyotrophic ...mentioning
confidence: 99%